Pendidikan Agama Islam Pendekatan Sufistik Implikasinya Terhadap Pencegahan Perilaku Bullying - Khoeron, Khoeron; Tobroni, Tobroni; Faridi, Faridi (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2023)
Education aims to increase human intellectual, emotional and spiritual potential. Problems that arise from the world of education, such as brawls between students, murders, especially among teenagers, of course cannot be separated from the bitterness of the knowledge gained. The aim of this article is to discuss efforts to prevent bullying behavior among students using a Sufistic approach. This research method uses descriptive qualitative by obtaining data from scientific literature and campus media sources as research objects. Therefore, in this case, as a step in developing Islamic religious education, it is very important to discuss spiritual aspects which are part of human intelligence through a Sufi approach as a conceptual basis in efforts to prevent bullying behavior. The results of this research explain that the Sufistic approach in learning Islamic religious education can be implemented in stages through riyadlah (soul training) by paying attention to the student's condition. The riyadlah process can be carried out by applying various Sufism or Sufism learning materials which can be an instrument for forming strong character, minimizing inequality and creating an inclusive atmosphere in the educational environment